2022
DOI: 10.1021/acs.orglett.2c00048
|View full text |Cite
|
Sign up to set email alerts
|

(Fluoromethylsulfonyl)methylation of Quinoxalinones Using NaSO2CH2F for C–F Bond Cleavage

Abstract: We developed a facile, efficient, and scalable route to achieve monofluoromethylsulfinyl alkylation of quinoxalinones. NaSO 2 CH 2 F served as the source of methylene to construct new C−C and C−S bonds via C−F bond cleavage. NaSO 2 CH 2 F was also the source of SO 2 CH 2 F. Density functional theory calculations confirmed the proposed mechanism, in which the SO 2 CH 2 F radical is immediately trapped. The reaction exhibited a high level of atom economy. Moreover, some representative products displayed excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…To further examine the involvement of FSO 2 radicals in the reaction, a radical-clock experiment was conducted with diethyl 2,2-diallymalonate 7 , a well-known radical probe, and the cyclized product 8 can be isolated in 20% yield (Figure A-2), which is consistent with a radical mechanism. On the basis of the above results and previous reports, , we proposed a possible mechanism for this radical 1-fluorosulfonyl-2-heteroarylation reaction (Figure B). First, under the irradiation of blue LEDs, the photocatalyst (ODA) is excited and undergoes a single electron transfer (SET) to the redox-active radical precursor 2a .…”
supporting
confidence: 78%
See 1 more Smart Citation
“…To further examine the involvement of FSO 2 radicals in the reaction, a radical-clock experiment was conducted with diethyl 2,2-diallymalonate 7 , a well-known radical probe, and the cyclized product 8 can be isolated in 20% yield (Figure A-2), which is consistent with a radical mechanism. On the basis of the above results and previous reports, , we proposed a possible mechanism for this radical 1-fluorosulfonyl-2-heteroarylation reaction (Figure B). First, under the irradiation of blue LEDs, the photocatalyst (ODA) is excited and undergoes a single electron transfer (SET) to the redox-active radical precursor 2a .…”
supporting
confidence: 78%
“…A subsequent 1,2-hydrogen shift and single electron oxidation by the radical cations of ODA give the cationic intermediate ( Int-C ). Finally, the desired product 4 is generated through deprotonation …”
mentioning
confidence: 99%
“…The application of NaSO 2 CH 2 F as a monofluoromethylation reagent has been somewhat limited due to the use of silver salts and a large excess of strong oxidants in a poorly controlled radical generation. 18 We found that 2-vinylnaphthalene 1a and benzoyl fluoride 2a could react with NaSO 2 CH 2 F in the presence of NHC catalyst N2 (cycloheptane-fused thiazolium salt), 19 photocatalyst Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 and base Cs 2 CO 3 upon blue LED irradiation to afford the acylmonofluoromethylation product 3a in 11% yield (Table 1, entry 1). Screening of NHC catalysts with different scaffolds such as triazolylidenes N19 and N22 , imidazolylidenes N33 and CAACs N34 revealed that N22 gave the highest yield (Table 1, entries 2–5).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to C-F bond formation, [49][50][51][52] the use of AuF complexes in the activation of the C-F bond is yet to be reported, [53][54][55][56] although AuF complexes have long been proposed as important intermediates. 31,34 In continuation of our interest in metal-catalyzed C-F transformation, [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] we prepared Au(I) bifluoride supported by the 9,9-dimethyl-4,5-bis(ditert-butylphosphino)xanthene ( t BuXantphos) ligand whose ligand strain may promote the elongation of the Au-X bond. Interestingly, the newly prepared Au(I) bifluoride complex exhibited dramatically enhanced catalytic activity toward HDF and hydrosilylation of CO 2 with a 6-or 16-times increase than its Au(I) chloride counterpart, respectively.…”
Section: Introductionmentioning
confidence: 99%